Perforated duodenal ulcer after gastric bypass: a challenging diagnosis - Amaral, Maria J.; Serôdio, Marco; Fraga, Emília C.; Camacho, Cristina P.; Almeida, Ana C.; Manso, António; Tralhão, José G. (International Surgery Journal, 2020)
Roux-en-Y gastric bypass (RYGB) is one of the most commonly performed surgeries for morbid obesity. Perforated duodenal ulcers are very rare in these patients (with a 0.25% incidence reported) and the diagnosis can be challenging. We report a case of a 43-year-old woman who presented with severe acute abdominal pain to the emergency department. She had undergone a laparoscopic RYGB 5 years previously. Exploratory laparoscopy revealed a duodenal perforation, which was repaired by primary closure. As Helicobacter pylori has been implicated in the formation of ulcers in this population, eradication therapy should be started.